Effect of codeine on CYP450 isoform activity of rats - Shuanghu Wang; Yanwen Dong; Ke Su; Jing Zhang; Linyi Wang; Anyue Han; Congcong Wen; Xianqin Wang; Yan He (Taylor & Francis Group, 2017)
Context: Codeine, also known as 3-methylmorphine, is an opiate used to treat pain, as a cough medicine and for diarrhoea. No study on the effects of codeine on the metabolic capacity of CYP enzyme is reported. Objective: In order to investigate the effects of codeine on the metabolic capacity of cytochrome P450 (CYP) enzymes, a cocktail method was employed to evaluate the activities of CYP2B1, CYP2D1, CYP1A2, CYP3A2 and CYP2C11. Materials and methods: Sprague-Dawley rats were randomly divided into codeine group (low, medium, high) and control group. The codeine group rats were given 4, 8, 16 mg/kg (low, medium, high) codeine by continuous intragastric administration for 14 days. Five probe drugs bupropion, metroprolol, phenacetin, midazolam and tolbutamide were given to rats through intragastric administration, and the plasma concentrations were determined by UPLC-MS/MS. Results and conclusion: The pharmacokinetic parameters of bupropion and metroprolol experienced obvious change with AUC(0-t), Cmax increased and CL decreased for bupropion in medium dosage group and midazolam low dosage group. This result indicates that the 14 day-intragastric administration of codeine may inhibit the metabolism of bupropion (CYP2B1) and midazolam (CYP3A2) in rat. Additional, there are no statistical differences for albumin (ALB), alkaline phosphatase (ALP), creatinine (Cr) after 14 intragastric administration of codeine, while alanine aminotransferase (ALT), aspartate aminotransferase (AST), uric acid (UA) increased compared to control group. The biomedical test results show continuous 14 day-intragastric administration of codeine would cause liver damage.